Transcriptome profiling of stevia rebaudiana ms007 revealed genes involved in flowedevelopment - Nurul Hidayah, Samsulrizal; Khairul Shahyidi, Khadzran; Meenakshi Sundram, Tamil Chelvan; Zarina, Zainuddin; Siti Hajar Noor, Shaarani; Nur Sabrina, Ahmad Azmi; Sarahani, Harun (TUBITAK, 2021)
Stevia rebaudiana is a medicinal plant recommended to diabetic or obese patients as an alternative sweetener owing to its low-calorie property. Previous studies have found that the stevioside level is highest at the time of flower bud formation and lowest at the time of preceding and following flower bud formation. Hence, this study aims to identify the genes involved in the flowering of local S. rebaudiana accession MS007 by investigating the transcriptomic data of two stages of growth, before flowering (BF) and after flowering (AF) that were deposited under accession number SRX6362785 and SRX6362784 at the NCBI SRA database. The transcriptomic study managed to annotate 108299 unigenes of S. rebaudiana with 8871 and 9832 genes that were differentially expressed in BF and AF samples, respectively. These genes involved in various metabolic pathways related to flower development, response to stimulus as well as photosynthesis. Pheophorbide A oxygenase (PAO), eukaryotic translation initiation factor 3 subunit E (TIF3E1), and jasmonate ZIM domain-containing protein 1 (JAZ1) were found to be involved in the flower development. The outcome of this study will help further research in the manipulation of the flowering process, especially in the breeding programme to develop photo-insensitive Stevia plant.